2012
DOI: 10.1159/000336404
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Acne: Therapeutic Potential of Ketogenic Diets

Abstract: The influence of nutrition on skin health is a growing research area but the findings of various studies on the effect of diet on the development of acne have often been contradictory. The general opinion among researchers has oscillated between two different, opposing positions: that diet either is or is not a key factor for acne development. This review examines the evidence supporting an influence of various dietary components on the development of acne particularly focusing on the role played by carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 179 publications
(94 reference statements)
0
25
0
1
Order By: Relevance
“…Paoli et al . also supported the influence of various dietary components on the development of acne, focusing particularly on the role played by carbohydrates …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Paoli et al . also supported the influence of various dietary components on the development of acne, focusing particularly on the role played by carbohydrates …”
Section: Discussionmentioning
confidence: 87%
“…These findings are also consistent with Smith et al ., who demonstrated that a low‐glycaemic‐load diet for 12 weeks decreased serum IGF‐1 levels and significantly improved acne. The study by Paoli et al . demonstrated that high‐glycaemic‐load diets aggravate acne, cause postprandial hyperinsulinaemia and increase serum levels of free IGF‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Placebo‐controlled studies have demonstrated that high glycaemic load diets aggravate acne, result in postprandial hyperinsulinaemia and increase serum levels of free IGF‐1 . Epidemiological as well as clinical evidence confirmed that milk and other insulinotropic dairy products induce or aggravate acne .…”
Section: Western Diet Upregulates Insulin/igf‐1 Signallingmentioning
confidence: 99%
“…Since ketogenic diet (KD) was established in the 1920s to treat epilepsy [1], it has been under investigation for many years as a potential therapy for numerous other diseases, such as Parkinson's disease, Alzheimer's disease, acne, and diabetes [2][3][4][5][6]. In the context of tumor therapy, KD has been propounded to potentiate antitumor effects of chemotherapy or radiation and to simultaneously reduce needed dosages to increase the quality of life of patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%